1999
DOI: 10.1143/jjap.38.5750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microstructure and Crystal Structure of Polycrystalline Silicon Exhibiting Varied Textures Fabricated by Microwave and Very High Frequency Plasma Enhanced Chemical Vapor Deposition and Their Transport Properties

Abstract: The complexity of a system, in general, makes it difficult to determine some or almost all matrix elements of its operators. The lack of accuracy acts as a source of randomness for the matrix elements which are also subjected to an external potential due to existing system conditions. The fluctuation of accuracy due to varying system conditions leads to a diffusion of the matrix elements. We show that, for single-well potentials, the diffusion can be described by a common mathematical formulation where system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
(33 reference statements)
2
9
0
Order By: Relevance
“…As Kamiya et al report, the growth of the ͑400͒ oriented poly-Si depends significantly on the growth surface structure. 13,38 Under conditions where ͑220͒ oriented poly-Si films are grown, the grain height tends to decrease with an increasing hydrogen mixing ratio, which is similar to the result obtained with a SiH 4 /H 2 system. 39 In low-temperature PECVD system using H 2 and SiH 4 gases, the majority of the growth surface is covered with hydrogen under high hydrogen mixing ratio conditions.…”
Section: Growth Mechanism Of C-si:h and Relationship Between Film supporting
confidence: 78%
See 3 more Smart Citations
“…As Kamiya et al report, the growth of the ͑400͒ oriented poly-Si depends significantly on the growth surface structure. 13,38 Under conditions where ͑220͒ oriented poly-Si films are grown, the grain height tends to decrease with an increasing hydrogen mixing ratio, which is similar to the result obtained with a SiH 4 /H 2 system. 39 In low-temperature PECVD system using H 2 and SiH 4 gases, the majority of the growth surface is covered with hydrogen under high hydrogen mixing ratio conditions.…”
Section: Growth Mechanism Of C-si:h and Relationship Between Film supporting
confidence: 78%
“…We have reported a similar discrepancy between scanning electron microscopy ͑SEM͒ observation and XRD analysis for ͑220͒ oriented poly-Si. 13 This is because the large grains observed by SEM consist of smaller single-domain crystallites which are observed by XRD: i.e., the larger grains have small secondary structures. Similarly, it is thought that the Raman analysis provides grain sizes of the smaller singledomain crystallites and that the c-Si:H contains small grains with size of ϳ3 nm independent of film thickness, suggesting that new nuclei are formed at/near the growth surface during the film deposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It indicates that each crystalline grain ("K" and "L" in the figure) is spherical and smaller than the large corn-shaped structure. This type of secondary microstructure feature is often observed in µc-Si:H [8,9]. From high resolution TEM, we confirmed that the smaller structures corresponded to single-domain crystalline silicon grains 4 nm -8 nm in size.…”
Section: Results and Discussion Film Structuresupporting
confidence: 72%